2021
DOI: 10.1001/jamasurg.2021.4904
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Racial, Ethnic, and Sex Representation Among Surgical Faculty Members and Medical Students in the US, 2011-2020

Abstract: Diversity in medicine improves patient outcomes and decreases health disparities. [1][2][3] Despite ongoing diversity, equity, and inclusion initiatives, however, several groups remain underrepresented in medicine (URIM). In 2021, Zhu et al 4 reported racial disparities among Black and Hispanic academic surgeons with little change over the past 12 years. Among medical schools in the US, the proportion of female matriculants has increased over time and ultimately surpassed male matriculants in 2017. 5 However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Diversity in the surgical workforce is critical to promote diverse perspectives and innovation, 37 and diverse faculty have a positive effect on the diversity of residents and medical students. 38,39 However, despite this benefit, the growth in female representation in surgery is incremental, whereas there has been little to no change in representation of racial and ethnic minority surgical residents. 38,40 Furthermore, representation of women and URiM faculty in leadership positions is even more inequitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity in the surgical workforce is critical to promote diverse perspectives and innovation, 37 and diverse faculty have a positive effect on the diversity of residents and medical students. 38,39 However, despite this benefit, the growth in female representation in surgery is incremental, whereas there has been little to no change in representation of racial and ethnic minority surgical residents. 38,40 Furthermore, representation of women and URiM faculty in leadership positions is even more inequitable.…”
Section: Discussionmentioning
confidence: 99%
“…It is as important that we actively address these barriers by creating a more inclusive and diverse surgical workforce. Diversity in the surgical workforce is critical to promote diverse perspectives and innovation, 37 and diverse faculty have a positive effect on the diversity of residents and medical students 38,39 . However, despite this benefit, the growth in female representation in surgery is incremental, whereas there has been little to no change in representation of racial and ethnic minority surgical residents 38,40 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the authors of this paper sought to understand the impact of the diversity of surgical faculty on the diversity of medical students. We found that programs with more URiM faculty were more likely to have more URiM and female medical students 15 . We subsequently sought to expand our exploration in light of literature highlighting the complexity and importance of intersectionality in medical education research 13,14,16 .…”
mentioning
confidence: 99%
“…We found that programs with more URiM faculty were more likely to have more URiM and female medical students. 15 We subsequently sought to expand our exploration in light of literature highlighting the complexity and importance of intersectionality in medical education research. 13,14,16 Coined by legal scholar Crenshaw 17 in a landmark 1989 essay on the marginalization of Black women, "intersectionality" allows us to conceptualize mechanisms for discrimination, bias, and exclusion in the overlapping spaces of race and gender.…”
mentioning
confidence: 99%